The limits to 'global' social policy: The ILO, the social protection floor and the politics of welfare in East and Southern Africa. (April 2019) - Seekings, Jeremy
Bob Deacon's study of the Social Protection Floors initiative, led by the International Labour Organisation (ILO), entailed a pioneering study of the making of global social policy. Just how global is this 'global social policy' in terms of both its making and its subsequent diffusion? African governments were minimally involved in the making of this global social policy. Most seem to have acquiesced in this global policy-making, as they have with other 'global' declarations, in the expectation that it would have little effect on them. Nor, in Southern Africa, is there clear evidence of any significant effect. Even the social protection strategy documents adopted by either the African Union or national governments, typically written by external consultants, have generally avoided direct use of the concept of the social protection floor, while reiterating the commitment to 'comprehensive' (and appropriate) social protection that predated the ILO-led initiative. The trajectory of actual policy reform in Southern African countries does not appear to have changed. There continues to be a disjuncture between 'global social policy' at the global and African levels.